Real-time Identification of Electric Motor Faults Using Arduino - Sabri Alamsyah, Ilham; Elvanny Myori, Dwiprima; Yelfianhar, Ichwan; Hidayat, Rahmat (Journal of Industrial Automation and Electrical Engineering, 2024)
The reliability of electric motors is very important in various industries. Damage to electric motors caused by disturbances that are not detected early results in large losses, both in terms of time and cost. This research aims to design and build an Arduino-based electric motor fault detection device equipped with a PZEM-004t sensor, buzzer as an alarm, relay to turn off the motor when there is a disturbance and LCD I2C 16x2 to display the measured value. This tool is designed to provide protection to the motor from overvoltage, undervoltage and overcurrent disturbances. Based on the results of testing and analysis, the designed tool can detect and protect the motor from interference. The buzzer functions effectively as an alarm when the voltage and current values are close to the fault occurrence value. The relay can respond well in breaking the current in the motor when a disturbance occurs. Thus, this tool has the potential to be applied as a practical solution in preventing damage to electric motors in industrial environments